Waste heat recovery of the regenerator in a glass factory: a comparison of an analytical method and experiments - Duong , Ngoc Bich; Truong , Van Men; Le , Thanh Nhan; Lu , Jau-Huai; Nguyen , Kim Phung; Tran , Van Dien (Journal of Technical Education Science, 2020)
One of the excellent methods for recovering waste heat from combustion furnaces is using regenerators. However, regenerators used in the glass industry are complex systems owing to the transient nature of their operating cycle. In this work, the heat transfer characteristics of the regenerators in a glass melting furnace are numerically and experimentally studied. A one-dimensional heat transfer model is proposed to investigate the heat transfer characteristics of real regenerators. With the design and operating parameters based on experimental data obtained from a real glass factory, the numerical results show a relatively good agreement with the measured results. The trends of the outlet temperatures in heating and cooling processes obtained from the numerical study at the convergent condition are relatively consistent with the measurements. In addition, the difference in the thermal recovery efficiency of the regenerator between the numerical and experimental results is only 4.3%. Thus, the proposed simple model is a believable representation for predicting the heat transfer characteristics of the regenerator in the glass or steel industry.